A Study on Transverse Magnetic Wave Propagation Characteristics of Dielectric Wrapped Wire. Issue 1 (March 2020) - Meng, Fanbo; Li, Ran; Wang, Dongdong; Fu, Taiyi; Zhang, Tianshi; Feng, Beibei; Qiu, Sihai
Abstract: The transverse magnetic wave propagation characteristics of the dielectric wrapped wires are studied. The transverse magnetic wave transmission model of a dielectric wrapped wire is revised based on the variable seperation method. The spatial relationship between electromagnetic wave emission and reflection is obtained. An experiment is developed using the new actuator and coupler. The results show that the surface wave guide formed by a single wire wrapped in a low loss medium can ben used as a high speed data transmission channel.